Trinity and Grace in Augustine An Analysis of de Trinitate 8-10 in Light of de Spiritu et Littera. - Cheuk-Yin Yam, Colten (Augustinus - Werk und Wirkung Ser., 2019)
This innovative study makes a fresh contribution to Augustine's study of grace and the Trinity. Through a close historical-contextual analysis of De trinitate 8-10 and De spiritu et littera, the dissertation demonstrates that a crucial pattern of 'love rescuing knowledge' can be seen to be present in both works. Augustine is also shown, in both works, to have a keen interest in discussing the theme of human perfection.In uncovering linkages between Augustine's reflections on grace and the Trinity in these works, as well as in his other writings, this study makes the wider claim that these two famous theological themes should be explored in concert with one another, rather than be treated separately. The nascent Pelagian controversy is considered as an important historical background, and the dissertation makes use of the most up-to-date scholarship on Platonism and biblical exegesis.